Cysticercosis of the central nervous system: clinical and therapeutic considerations. Issue 8 (August 1984) - Torrealba, G; Del Villar, S; Tagle, P; Arriagada, P; Kase, C S
Abstract : In a group of forty cases of cysticercosis of the central nervous system, 59% presented with intracranial hypertension due to obstructive hydrocephalus. Ventricular or cisternal cysts, and chronic cysticercus meningitis were the most common causes of hydrocephalus. Seizures occurred in 40% of the patients, in one-half of them in association with CT-detected parenchymatous cysts. In 20% of the cases progressive mental deterioration was the main clinical feature, at times associated with hydrocephalus. CT scan provided the highest diagnostic yield, being abnormal in 90% of cases. Long term prognosis was poor, with a mortality rate of 38% over a 40-month follow-up period. The most common cause of death (60%) was meningitis. CSF shunting is the treatment of choice for hydrocephalus, irrespective of its mechanism. Surgical resection is indicated in some cases with a single superficial (cortical) or posterior fossa cyst. Supratentorial cysts carry a relatively benign prognosis.